(3cJGH aj GdgjFIs ((3eMeO Hf eDjO GdZQV GdYGeQi s)
(3ChdgG (B:s
(3GdMeO dhLhH PGJg hjSJhLH GdTcQ aGf GdYbhd eJWGHbI hGdCdHGH eJhGabI Ydi aVd GdYde s
(3BNQgG (B:s
(3hCeG GdchGcH GdHGbjI aEf GcKQgG de jhVY dgG GSekG adG JWjd Gdbhd HPcQgG hGddg GYde s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdadcs